Production of xylose from oil palm frond fibre by acid hydrolysis - Shalini, Maniarasan (2016)
Oil palm frond fibre (OPFF) is one of the oil palm biomass which is available in a large amount worldwide in oil palm plantation. Oil palm frond fibre (OPFF) is cheap, widely available, and has high potential to be a renewable source for the production of xylose. This paper presents the production of xylose from oil palm frond fibre by acid hydrolysis. The presence of xylose was tested using DNS analysis. In this research, diluted acid hydrolysis was applied for the treatment of oil palm frond fibre (OPFF) and several parameters including temperature (70, 85, and 100 °C), acid concentration (1, 3, and 5 M), and solid to liquid ratio (0.5 g:10 mL, 0.5 g:12.5 mL, and 0.5 g:15 mL) were taken into account in order to get the optimum conditions for xylose recovery from oil palm frond fibre (OPFF). The optimum xylose obtained was 1.0183 mg/mL under optimal conditions with acid concentration of 5M, temperature of 70 °C, and a solid to liquid ratio of 0.5 g:15 mL. Findings from this work is vital to produce xylose as the raw material for the production of xylonic acid and to make sure that we could find a solution for the abundance of oil palm frond fibre which might lead to environmental issues such as greenhouse gas emission and global warming.